Modified polyphenylene ether resin foam sheet

By adding specific proportions of phosphorus-based and halogen-based flame retardants to modified polyphenylene ether resin and using a batch foaming method, modified polyphenylene ether resin foamed sheets with controlled bubble diameter and density were prepared. This solved the problems of insufficient dielectric properties and flame retardancy in existing technologies, and realized foamed sheets with low dielectric properties and excellent flame retardancy in high-frequency circuits, meeting the UL94 standard.

CN119487110APending Publication Date: 2025-02-18FURUKAWA ELECTRIC CO LTD

Patent Information

Application Number
CN202480003219.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-03-15
Filing Date
2024-01-22
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Existing modified polyphenylene ether resin foam materials face challenges in controlling bubble diameter and achieving excellent surface properties. They struggle to simultaneously meet the requirements of low dielectric properties, flame retardancy, and good formability in high-frequency circuits, and fail to meet or exceed the V-1 standard in UL standard flame retardancy tests.

Method used

By adding specific proportions of phosphorus-based and halogen-based flame retardants to modified polyphenylene ether resin and using a batch foaming method to control the bubble diameter within the range of 1–30 μm and the bubble number density within the range of 1.8 × 10⁴–9 × 10⁸ bubbles/mm³, combined with micro-foaming technology, modified polyphenylene ether resin foam sheets with a relative permittivity of 1.10–2.00 and a dielectric loss factor of 0.5 × 10⁻³–2.5 × 10⁻³ are prepared.

Benefits of technology

A modified polyphenylene ether resin foam sheet with low dielectric constant and low dielectric loss for high-frequency circuits has been developed. It has excellent surface properties and flame retardancy, meeting the flame retardancy levels of V-0 and V-1 of UL94 standard. It is suitable for housings of electrical and electronic components, electrical insulation materials, sealing materials, and substrates for electromagnetic wave control components for high-frequency applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005212549880000101
    Figure BDA0005212549880000101
  • Figure BDA0005212549880000121
    Figure BDA0005212549880000121
  • Figure BDA0005212549880000131
    Figure BDA0005212549880000131
Patent Text Reader

Abstract

The present invention provides a modified polyphenylene ether resin foam sheet which has good moldability, a very low relative dielectric constant and a very low dielectric loss factor at high frequencies, self-extinguishing properties or flame retardancy imparted thereto, and excellent surface properties. This modified polyphenylene ether resin foam sheet is obtained by foaming a modified polyphenylene ether resin containing a flame retardant, and has a relative dielectric constant of 1.10-2.00 and a dielectric loss factor (tan [delta]) in the range of 0.5 * 10 <-3 > to 2.5 * 10 <-3 >. The modified polyphenylene ether resin foamed sheet according to the present invention is a modified polyphenylene ether resin foamed sheet in which a modified polyphenylene ether resin foamed resin containing both a halogen-based flame retardant and a phosphorus-based flame retardant having a specific weight-average molecular weight is foamed. And the average bubble diameter and the bubble number density of the modified polyphenylene ether resin foam sheet are within predetermined ranges.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a modified polyphenylene ether resin foamed sheet. Background Art

[0002] There is a demand for a resin material that can be used as a housing of a member of an electric component or an electronic component, and can also be applied as an electric insulating material, a sealing material, a protective material, or a substrate for a high-frequency electromagnetic wave control member.

[0003] Polyphenylene ether (hereinafter, sometimes referred to as PPE) resins are widely used in the field of electronic devices, etc. due to their excellent flame retardancy, thermal stability, hot water resistance, and electrical properties. However, since the melt fluidity of polyphenylene ether resins is extremely low, they are alloyed with other resins during molding. Among them, since polystyrene is completely miscible with polyphenylene ether, they are alloyed without a compatibilizer and are commercially sold as "modified polyphenylene ether resins." Since the material after alloying the polystyrene is easy to mold, has excellent balance of heat resistance or mechanical strength, and is also easy to flame retardant, it is widely used. Here, regarding polystyrene, it is sometimes recorded as PS in the specification below for convenience.

[0004] In particular, in the electrical and electronic fields, alloys with polystyrene resins are evaluated for heat resistance, flame retardancy, dimensions, etc., and are used in flyback transformer boxes, coil frames, relay sockets, adapter boxes, switches, etc. However, when the modified polyphenylene ether resin is foamed, although the flame retardancy is more excellent than that of conventional foams, it still does not meet the standard of V-1 or above in the flame retardancy test of the UL standard due to the reasons described below.

[0005] Modified polyphenylene ether resins have previously been used as foams that exert such higher properties, for example, a foam formed by a bead foaming method as described in Patent Document 1 is known. Although the resin foam of Patent Document 1 has excellent flame retardancy and antistatic properties for use in electronic equipment or automotive components, there is no specific disclosure of bubble structure, dielectric properties, and surface properties such as bubble diameter or bubble density. In addition, although Patent Document 2 is known to disclose a method for obtaining a modified polyphenylene ether resin foam containing a phosphate ester compound and having high heat resistance and flame retardancy, it is also not disclosed in detail about the bubble structure, dielectric properties, and surface properties. In addition, although Patent Document 3 is known to disclose a method for obtaining a hollow foam blow molded body, the foam blow molded body of Patent Document 3 cannot obtain a foam sheet having a plate thickness thicker than that of the present invention. Such foams do not have the purpose of controlling the bubble structure of the foam to obtain a foam with excellent dielectric properties and surface properties.

[0006] Furthermore, Patent Document 4 discloses a substrate foam, which is a resin having at least one of a crystalline melting temperature, a glass transition temperature, and a liquid crystal transition temperature of 260°C or more, and a non-crystalline resin such as a modified polyphenylene ether having a glass transition temperature of 230°C or less, mixed in a specified ratio and foamed by batch foaming, and the bubble diameter is 0.3 to 1.5 μm. However, the relative dielectric constant of the foam is 2.6 to 2.9, which is greater than that of the present invention. This is because the foaming ratio of the resin in the invention of Patent Document 4 is small, so it is impossible to achieve a smaller relative dielectric constant by introducing fine bubbles at a high density. That is, in order to reduce the relative dielectric constant, it is necessary to increase the bubble density while maintaining fine bubbles.

[0007] In addition, Patent Document 5 discloses a laminated foam body, the auxiliary layer on the back of which is a foam body. Although the invention records the relative dielectric constant in the frequency band of 79 GHz and 29 GHz, the relative dielectric constant is in the range of 2.28 to 2.73, and the dielectric loss factor tanδ is in the range of 0.002 to 0.0077. The bubble diameter is 44 to 103 μm, and the foaming ratio is 9.2 to 30.8 times. In the case of Patent Document 5, the bubble diameter exceeds 30 μm, the foaming ratio is also high, and the relative dielectric constant exceeds 2.0, so the dielectric properties are hardly excellent. Although Patent Document 6 records the use of various bubble nucleating agents to produce foams with bubble diameters of less than 20 μm and more than 10 μm by a batch method, the invention involved in this document requires bubble nucleating agents and is not related to modified PPE foams, and its purpose is not to improve dielectric properties. Patent document 7 discloses a PPS (Polyphenylene Sulfide) resin foam using batch foaming and adding a crosslinking agent, and the problem is to provide a polyphenylene sulfide foam and a method for manufacturing the same which not only maintain the basic properties of the PPS resin but also have excellent secondary moldability. Regarding the PPS resin foam, it is recorded that the average bubble diameter can be less than 20 μm. As known from patent documents 6 and 7, when a microbubble structure is obtained by using batch foaming, in order to control the bubble structure, a bubble nucleating agent or a crosslinking agent needs to be used accordingly.

[0008] On the other hand, since the modified polyphenylene ether resin has a good balance between high flame retardancy and low dielectric properties as described above, it is expected to be used in high-frequency-related components, and the foam is expected to be used in megahertz wave components that are expected to expand in the future. However, if the same low dielectric properties are to be exerted for megahertz waves, the foam needs to have fine bubbles of at least 30 μm or less, and as much as possible less than 10 μm, in consideration of the loss caused by reflection and scattering when radio waves in the megahertz band are transmitted. [Prior art literature] [Patent Document]

[0009] [Patent Document 1] Japanese Patent No. 5642521 [Patent Document 2] Japanese Patent Application Publication No. 2017-155196 [Patent Document 3] Japanese Patent No. 6106420 [Patent Document 4] Japanese Patent Application Publication No. 2008-303247 [Patent Document 5] Japanese Patent Application Publication No. 2021-136540 [Patent Document 6] Japanese Patent No. 3138488 [Patent Document 7] Japanese Patent No. 5809895 Summary of the invention [Problems to be solved by the invention]

[0010] Although the bubble diameter is not described in Documents 1 and 2, generally speaking, the methods described in these documents are difficult to inhibit bubble growth, and therefore cannot make the bubble diameter thinner and the surface properties better. Although Document 1 uses a bead foaming molding, and Document 2 also assumes the same means, it is difficult to make a sheet by bead foaming, and even if it is made into a sheet, it is not conducive to considering, for example, bonding with copper foil, because there are interfaces between particles.

[0011] When the modified polyphenylene ether resin is foamed, the contact area with air increases, the combustion speed increases, and the flame retardancy decreases. Therefore, it is generally difficult to meet the vertical flame retardancy required in high-frequency related fields. Therefore, although the fine foam sheet using the modified polyphenylene ether resin has excellent flame retardancy compared with the common foam resin sheet, it still does not meet the standard of V-1 or above in the flame retardancy test of the UL standard.

[0012] Since the contact between air and resin increases in the foamed body compared to the unfoamed body, the flame retardancy is significantly reduced. The part of the resin that is less in the foamed body than in the unfoamed body is easily softened by the heat of combustion, resulting in the resin being easily crushed during combustion. On the other hand, if the amount of flame retardant added to the foamed body is increased in order to improve the flame retardancy, the flame retardant usually causes foaming hindrance, so the foamed body with the target bubble diameter or density cannot be obtained, and at the same time, the surface properties of the foamed body are reduced in some cases.

[0013] Therefore, it is very difficult to obtain a foamed body of a modified polyphenylene ether resin foam sheet that not only satisfies the molding processability of a molded body, but also satisfies the requirements of easy complex and fine foaming, and satisfies the requirements of improved lightweight and flame retardancy, and excellent surface properties. Therefore, the object of the present invention is to obtain a foamed body of a modified polyphenylene ether resin foam sheet that has good molding processability, very low relative dielectric constant and dielectric loss factor at high frequencies, self-extinguishing or flame retardancy, and excellent surface properties. [Solution to the problem]

[0014] The modified polyphenylene ether resin foamed sheet of the present invention is a sheet formed by foaming a modified polyphenylene ether resin containing a flame retardant, and has a relative dielectric constant of 1.10 to 2.00 and a dielectric loss factor (tan δ) of 0.5×10 -3 ~2.5×10 -3 range. The modified polyphenylene ether resin foamed sheet of the present invention may have an arithmetic mean surface roughness Ra of 0.50 μm or less. Here, even if only a predetermined amount of phosphorus-based flame retardant is included as the flame retardant, it is confirmed that there is an effect of improving flame retardancy, so the modified polyphenylene ether resin foam sheet can also be made into a modified polyphenylene ether resin foam sheet containing only phosphorus-based flame retardant as the flame retardant. The modified polyphenylene ether resin foam sheet may include both a halogen-based flame retardant and a phosphorus-based flame retardant having a weight average molecular weight of 1,000 to 1,000,000 as the flame retardant. As described above, if the phosphorus-based flame retardant and the prescribed halogen-based flame retardant are used in appropriate amounts, foaming inhibition can be prevented as described later, and the flame retardancy can be further improved to a level that satisfies the UL standard. In addition, the relative dielectric constant of the modified polyphenylene ether resin foamed sheet can also be 1.20 to 1.57, and the dielectric loss factor (tan δ) can also be 1.0×10 -3 ~2.1×10 -3 range.

[0015] The modified polyphenylene ether resin foam sheet of the present invention may also be a modified polyphenylene ether resin foam sheet, wherein the modified polyphenylene ether resin foam sheet is formed by foaming a modified polyphenylene ether resin containing a halogen flame retardant and a phosphorus flame retardant as a flame retardant having a weight average molecular weight of 1,000 or more, and the average bubble diameter of the bubbles in the modified polyphenylene ether resin foam sheet is 1 to 30 μm, and the bubble number density is 1.8×10 4 ~9×10 8 Pieces / mm 3 . As described above, the cell structure of the modified polyphenylene ether resin foamed sheet is such that the average cell diameter is in the range of 1 to 30 μm and the cell number density is 1.8×10 4 ~9×10 8 Pieces / mm 3 As a result, dielectric properties such as relative dielectric constant and dielectric loss factor tanδ within the said range can be obtained. In addition, in the modified polyphenylene ether resin foamed sheet, the average bubble diameter of the bubbles in the modified polyphenylene ether resin foamed sheet may be 1 to 22 μm, and the bubble number density may be 2.0×10 4 ~8×10 8 Pieces / mm 3 In this way, by making the average cell diameter finer and further increasing the lower limit of the cell number density, the dielectric properties and surface properties of the foamed sheet can be further improved. Regarding flame retardancy, when only an inorganic flame retardant such as a phosphorus flame retardant is added, the addition of the flame retardant can improve the flame retardancy and impart self-extinguishing properties during combustion, but if the amount of the flame retardant added increases, it will hinder the foaming properties, so it is difficult to foresee the effect of further improving the flame retardancy. Even if a specific halogen flame retardant is added to the phosphorus flame retardant as a flame retardant, if the polymer flame retardant of the specified molecular weight is not used and the composition range of the flame retardant is further adjusted to the specified range, it is impossible to meet the V-0 and V-1 standards in the flame retardant test of the UL94 standard without affecting the foaming state, and it is impossible to maintain the same average bubble diameter and bubble density as when no flame retardant is added. Here, regarding flame retardancy, its purpose is to improve flame retardancy without causing foaming hindrance. Specifically, its purpose is to obtain the following foam body, first, by adding a flame retardant, although it is flammable, it is given self-extinguishing property to reduce flammability, and further, second, the flame retardancy level is improved to a level that meets the V-0 and V-1 standards in the flame retardant test of the UL94 standard.

[0016] Here, it is generally difficult to make the average bubble diameter fine and the bubble density within a specified range as described above in other manufacturing methods such as bead foaming, injection foaming, and extrusion foaming (cross-linked foaming, non-cross-linked foaming), resulting in the difficulty in obtaining the bubble structure. In addition, even if a material having the bubble structure and dielectric properties is successfully obtained by using other manufacturing methods other than the fine foaming method of the present invention, when the other foaming methods are used for manufacturing, the bubble diameter distribution of the foam is large, and it is difficult to maintain the surface properties of the foamed sheet in an excellent state, so it is difficult to suppress the surface roughness Ra (arithmetic mean surface roughness) of the foamed sheet to a range below 0.50 μm.

[0017] As described above, the arithmetic mean surface roughness Ra of the modified polyphenylene ether resin foam sheet of the present invention may also be less than 0.50 μm. In addition, when the lower limit of the arithmetic mean surface roughness Ra of the surface of such a modified polyphenylene ether resin foam sheet is considered, the high-frequency characteristics such as the skin effect can be further improved by suppressing the arithmetic mean surface roughness Ra to 0.08 to 0.50 μm, preferably 0.10 to 0.40 μm, and more preferably 0.10 to 0.30 μm. Therefore, it is further preferably used for substrate applications such as high-frequency circuits.

[0018] The average thickness of the modified polyphenylene ether resin foamed sheet is a modified polyphenylene ether resin foamed sheet with an average thickness of 0.05mm to 2.0mm that can be manufactured, and the average thickness of the sheet can also be 0.1mm to 2.0mm. Compared with bead foaming, extrusion cross-linking foaming, extrusion gas foaming, etc., the average thickness of the modified polyphenylene ether resin foamed sheet of the present invention is a batch foaming method that separates the forming step from the foaming step to foam the product, and further can independently control the penetration and foaming of the foaming gas, so it is believed that the thickness of the foamed sheet can be thinned. Therefore, the upper limit of the foamed sheet is 2mm, and as for the lower limit, even if the sheet thickness becomes thinner, since the surface layer is formed on the upper and lower sides of the sheet, the lower limit of the foamed sheet must be at least 50μm (0.05mm). At this time, after the fine foaming method is completed, rolling can be performed as needed to adjust the thickness and surface properties.

[0019] The modified polyphenylene ether resin foam sheet was tested according to the UL-94 vertical method (20 mm vertical combustion test) of the U.S. UL standard, and the flame retardancy was evaluated. As far as the test results are concerned, the modified polyphenylene ether resin foam sheet meets the V-0 and V-1 standards of the modified polyphenylene ether resin foam sheet as expected. The material to which the flame retardant is added within the scope of the present invention to the base resin meets the V-0 and V-1 standards of the following UL-94, but when the flame retardant is not added or the amount of the flame retardant added does not meet the scope of the present invention, the flame retardancy cannot meet the V-0 and V-1 of the UL-94 vertical method of the U.S. UL standard.

[0020] The modified polyphenylene ether resin foam sheet may be a modified polyphenylene ether resin foam sheet used for electric component housings, electronic component housings, electric insulating materials, sealing materials, protective materials, or substrates for high-frequency electromagnetic wave control components.

[0021] (About the mixing of modified polyphenylene ether resin and polystyrene resin) Here, the reason for mixing the polystyrene resin with the polyphenylene ether resin is that although the polyphenylene ether resin has excellent heat resistance and strength, it has low processability and cannot be processed, so it is necessary to improve the processability. Here, the reason for setting the blending amount of the polyphenylene ether resin to 40% by mass or more and 80% by mass or less is that if the blending amount of the polyphenylene ether resin is less than 40% by mass, the target heat resistance or strength, etc. cannot be obtained, and the reason for setting it to 80% by mass or less is that if it exceeds 80% by mass, the processability becomes low. In addition, generally, the blending amount of the polystyrene resin is the remaining amount of the polyphenylene ether resin, so the blending amount of the polystyrene resin is 20% by mass or more and 60% by mass or less, and it is a well-known fact that the polystyrene resin is mixed with the polyphenylene ether resin and mixed at the above ratio. By adding a flame retardant to the modified polyphenylene ether resin foam sheet, a polyphenylene foam sheet having self-extinguishing property to reduce flammability or improved flame retardancy and excellent dielectric properties and surface properties can be obtained. Finally, by adding a halogen flame retardant and a phosphorus flame retardant at the same time, the flame retardancy can be further improved, and the V-0 and V-1 standards can be met in the flame retardancy test of the UL94 standard. The reason is that a synergistic effect is obtained by using the two at the same time.

[0022] (Regarding the mixing of modified polyphenylene ether resin, polystyrene resin and phosphorus-based flame retardant) When the total amount of polyphenylene ether resin, polystyrene resin and phosphorus-based flame retardant is set to 100% by mass, taking strength, heat resistance or processability into consideration, the amount of polyphenylene ether resin in the mixture as a whole is roughly the same as that in the case where no phosphorus-based flame retardant is contained and the modified polyphenylene ether resin and polystyrene resin are mixed, which is 40% to 80% by mass. Therefore, the total amount of polystyrene and phosphorus flame retardant is 20% to 60% by mass, which is almost the same as the case of only mixing modified polyphenylene ether resin and polystyrene resin. Here, when the total content of polystyrene and phosphorus flame retardant takes the lower limit, the lower limits of polystyrene and phosphorus flame retardant are set to 15% by mass and 5% by mass, respectively. When the total content of polystyrene and the phosphorus-based flame retardant takes the upper limit value, the upper limits of polystyrene and the phosphorus-based flame retardant are set to 40% by mass and 20% by mass, respectively. The content of the polyphenylene ether resin, polystyrene resin, and phosphorus flame retardant at this time can be set to 40% by mass or more and 80% by mass or less, 15% by mass or more and 40% by mass or less, and 5% by mass or more and 20% by mass or less, respectively. In this case, the polystyrene resin and phosphorus flame retardant can be appropriately selected as long as the total amount of the polystyrene resin and the phosphorus flame retardant within the range is 100% by mass relative to the specified amount of polyphenylene ether resin. The reasons for setting the upper and lower limits of the blending amounts of the polyphenylene ether resin, the polystyrene resin, and the phosphorus-based flame retardant are described below. The reason for setting the blending amount of the polyphenylene ether resin to be 40% by mass or more and 80% by mass or less is that if the blending amount of the polyphenylene ether resin is less than 40% by mass, the target heat resistance or strength, etc. cannot be obtained, and the reason for setting it to be 80% by mass or less is that if it exceeds 80% by mass, the processability decreases, which is the same reason as the case of mixing only the modified polyphenylene ether resin and the polystyrene resin. Here, the reason for setting the blending amount of the polystyrene resin to be between 15 mass % and 40 mass % is that if it does not reach the lower limit, the processability is insufficient, and if it exceeds the upper limit, i.e. 40 mass %, the content of the polyphenylene ether resin is insufficient, and the performance such as heat resistance and strength is insufficient. Furthermore, when the total of the polyphenylene ether resin, the polystyrene resin and the phosphorus-based flame retardant used in the modified polyphenylene ether resin foamed sheet is taken as 100 mass %, the phosphorus-based flame retardant may be contained in an amount of 5 mass % to 20 mass %. In addition, the reason for setting the amount of the phosphorus-based flame retardant to be 5% by mass or more and 20% by mass or less is that, if the lower limit is not reached, carbonization (char) during combustion (a carbonized layer forming a three-dimensional structure through the solid phase during carbonization) is insufficiently formed, and interaction with the halogen-based flame retardant described later cannot be obtained. Even if the phosphorus-based flame retardant is added, the desired flame retardant performance cannot be ensured. If the upper limit is exceeded, the foaming property decreases. The reason why the total of polyphenylene ether resin, polystyrene resin and phosphorus flame retardant is set to 100 mass % instead of the total of polyphenylene ether resin and polystyrene resin is that they are usually mixed and commercially used. In this application, Zylon 340Z and 540Z of Asahi Chemical Industry are used as these materials.

[0023] As the flame retardant used in the modified polyphenylene ether resin sheet, a halogen flame retardant may be used as an oligomer or polymer flame retardant in addition to the phosphorus flame retardant. The specific halogen flame retardant may be added in an amount of 5 parts by mass or more and 40 parts by mass or less based on 100 parts by mass of the polyphenylene ether resin, the polystyrene resin, and the phosphorus flame retardant. Here, the composition of the base resin contains 5 mass % or more and 20 mass % or less of the phosphorus-based flame retardant based on 100 mass % of the polyphenylene ether resin, the polystyrene resin, and the phosphorus-based flame retardant. As a preferred form of the flame retardant of the modified polyphenylene ether resin foamed sheet, it can be exemplified as follows: when the total of polyphenylene ether resin, polystyrene resin and phosphorus flame retardant is set to 100% by mass, it contains 5% by mass or more and 20% by mass or less of phosphorus flame retardant, and relative to the total of polyphenylene ether resin, polystyrene resin and phosphorus flame retardant is 100 parts by mass, and further contains 5 parts by mass or more and 40 parts by mass or less of halogen flame retardant with a weight average molecular weight of 1,000 or more and 1,000,000 or less. As a result, the flame retardant system uses phosphorus flame retardant and halogen flame retardant. Its blending amount is ideally as described above. By adding halogen flame retardant within the range, foaming is ensured, and by combining the carbonization formation of phosphorus flame retardant, free radical capture and oxygen barrier effect by halogen flame retardant, it can show higher flame retardancy, and the foamed sheet meeting the V-0 and V-1 standards of UL94 standard as described below can be obtained.

[0024] The flame retardant used in the modified polyphenylene ether resin foam sheet preferably has a weight average molecular weight of 1,000 or more, more preferably 1,000 to 1,000,000. In this case, the flame retardant may be any of brominated carbonate oligomers or brominated polystyrene. By making the molecular weight of the halogen flame retardant greater than the lower limit, a good resin foam sheet without foaming hindrance can be obtained. By using such modified polyphenylene ether resin foamed sheet, the modified polyphenylene ether resin foamed sheet can be flame retardant. At this time, since preferably, if the weight average molecular weight of the flame retardant is 5,000 or more, it further stably acts, the average molecular weight of the flame retardant is further preferably 5,000 or more and 50,000 or less. In the case of brominated carbonate oligomers, it is preferably within the range, on the other hand, in the case of high-polymerization polymers such as brominated polystyrene, the upper limit is higher, preferably 1,000,000 or less. The reason is that if the molecular weight exceeds 1,000,000, bubble growth is inhibited, and it becomes difficult to obtain the desired expansion ratio and bubble density. [Effects of the Invention]

[0025] With regard to the modified polyphenylene ether resin foamed sheet, according to the present invention, a foamed sheet having good formability, very low relative dielectric constant and dielectric loss factor in high frequency, high flame retardancy, and excellent surface properties can be obtained. As a result, a low dielectric modified polyphenylene ether resin foamed sheet can be provided which can be used for housings for electrical parts, housings for electronic parts, electrical insulating materials, sealing materials, protective materials, substrates for high frequencies, or substrates for electromagnetic wave control components, and has excellent surface properties, self-extinguishing properties, or excellent flame retardancy. DETAILED DESCRIPTION

[0026] The modified polyphenylene ether resin foam sheet of the present invention contains a flame retardant. Examples of the flame retardant include a phosphorus flame retardant or a flame retardant containing a phosphorus flame retardant and a specific halogen flame retardant. The modified polyphenylene ether resin foam sheet of the present invention has a relative dielectric constant of 1.10 to 2.00 and a dielectric loss factor (tan δ) of 0.5×10 -3 ~2.5×10 -3 Alternatively, as another configuration of the present invention, a modified polyphenylene ether resin foam sheet is exemplified by foaming a modified polyphenylene ether resin containing a halogen flame retardant and a phosphorus flame retardant as a flame retardant, wherein the average bubble diameter of bubbles in the modified polyphenylene ether resin foam sheet is 1 to 30 μm, and the bubble number density is 1.8×10 4 ~9×10 8 Pieces / mm 3 First, as the resin composition of the preferred embodiment of the present invention, a modified polyphenylene ether resin containing polystyrene can be cited as an example, and this aspect is explained. Furthermore, the component composition of the phosphorus-based flame retardant and the specific halogen-based flame retardant is explained, and then the density of the resin, the bubble diameter, the manufacturing method and the physical properties of the foamed sheet are explained.

[0027] (Polyphenylene ether resin) Examples of the polyphenylene ether resin used in the present invention include a homopolymer composed of a repeating unit represented by the following general formula (1) and a copolymer containing a repeating unit represented by the following general formula (1). [Chemical formula 1] [Where R 1 , R 2 , R 3 , and R 4 Each independently represents a monovalent group selected from the group consisting of a hydrogen atom, a halogen atom, an alkyl group having 1 to 7 carbon atoms, a phenyl group, a haloalkyl group, an aminoalkyl group, and a hydrocarbyloxy group, and may be the same or different from each other; in addition, two adjacent groups may be bonded to each other to form a ring]

[0028] R in formula (1) 1 and R 4 More preferably, it is a linear or branched alkyl group having 1 to 6 carbon atoms, and more preferably, it is an alkyl group having 1 to 3 carbon atoms. Among them, methyl group and ethyl group are preferred. 2 and R 3 More preferred is a hydrogen atom or a linear or branched alkyl group having 1 to 6 carbon atoms, and more preferred is a hydrogen atom or an alkyl group having 1 to 3 carbon atoms. Among them, a hydrogen atom is preferred. The polyphenylene ethers may be used alone or in combination of two or more.

[0029] The molecular weight of the polyphenylene ether is not particularly limited, but the weight average molecular weight is preferably 10,000 to 30,000. In the present invention, "modification" means, for example, that the polyphenylene ether is alloyed with the polystyrene listed below, or that a predetermined functional group thereof is substituted at a specific position. In the modified polyphenylene ether resin foamed sheet of the present invention, it is preferred to use a modified polyphenylene ether resin obtained by mixing and alloying the polyphenylene ether and polystyrene. At this time, the mixing ratio of polyphenylene ether and polystyrene is not particularly limited. When the ratio of both polyphenylene ether and polystyrene and the phosphorus flame retardant is set to 100% by mass, it is preferred that the polyphenylene ether is set to 40% by mass or more and 80% by mass or less, and more preferably 50% by mass or more and 70% by mass or less.

[0030] (Polystyrene) In the present specification, examples of polystyrene resins include: homopolymers of styrene monomers such as styrene, α-methylstyrene, vinyltoluene, chlorostyrene, ethylstyrene, isopropylstyrene, dimethylstyrene, bromostyrene, or copolymers thereof; copolymers of a styrene monomer as a main component and a styrene monomer and a vinyl monomer that can be polymerized therewith; copolymers of a styrene monomer and a rubber component such as butadiene, homopolymers of a styrene monomer or copolymers thereof, or mixtures or polymers of a copolymer of a styrene monomer and a vinyl monomer and a diene rubber-like polymer, so-called high-impact polystyrene, etc., but are not limited thereto.

[0031] Examples of the polystyrene resin as a homopolymer include polystyrene, poly-α-methylstyrene, and polychlorostyrene. Examples of the polystyrene resin as a copolymer include styrene-butadiene copolymers, styrene-acrylonitrile copolymers, styrene-maleic acid copolymers, styrene-maleic anhydride copolymers, styrene-maleimide copolymers, styrene-N-phenylmaleimide copolymers, styrene-N-alkylmaleimide copolymers, styrene-N-alkylsubstituted phenylmaleimide copolymers, styrene-acrylic acid copolymers, styrene-methacrylic acid copolymers, styrene-methyl acrylate copolymers, styrene-methyl methacrylate copolymers, styrene-n-alkyl acrylate copolymers, styrene-n-alkyl methacrylate copolymers, and ethylvinylbenzene-divinylbenzene copolymers. In addition, examples include terpolymers such as ABS (Acrylonitrile Butadiene Styrene, acrylonitrile-butadiene-styrene) and butadiene-acrylonitrile-α-methylbenzene copolymers, but are not limited thereto.

[0032] In addition, graft copolymers are also included, for example, styrene grafted polyethylene, styrene grafted ethylene-vinyl acetate copolymer, (styrene-acrylic acid) grafted polyethylene, styrene grafted polyamide, etc. These may be used alone or in combination of two or more.

[0033] As a polystyrene resin, a weight average molecular weight of 180,000 to 500,000 is preferred. Furthermore, in this specification, the weight average molecular weight means that the weight average molecular weight is determined by gel permeation chromatography (GPC), using a calibration curve of the peak molecular weight of the chromatogram obtained by the determination of commercially available standard polystyrene (made using the peak molecular weight of standard polystyrene) to obtain the weight average molecular weight. Regarding the carrier and the chromatographic column, it is sufficient to select them according to the test object to be measured. As a carrier, for example, tetrahydrofuran (THF) can be cited. Furthermore, in this specification, when referring to the molecular weight of an oligomer or a polymer, unless otherwise specified, it means the one obtained by the method described. When the total amount of the polyphenylene ether resin, the polystyrene resin and the phosphorus-based flame retardant is set to 100 mass %, the polystyrene is preferably 15 mass % to 40 mass %, more preferably 15 mass % to 37 mass %, and most preferably 25 mass % to 35 mass %.

[0034] (Phosphorus flame retardant) The modified polyphenylene ether resin foamed sheet of the present invention preferably further contains a phosphorus-based flame retardant. If the phosphorus-based flame retardant is contained, it can exhibit self-extinguishing properties and obtain a higher flame retardancy improvement effect by interaction with the halogen-based flame retardant component described below.

[0035] As the phosphorus flame retardant, a phosphate compound is preferred. The phosphate compound is not particularly limited, but preferably has an effect as a flame retardant. In addition, the phosphate compound is preferably, for example, bisphenol A bis (diphenyl phosphate) or an aromatic condensed phosphate compound. As the phosphate compound, for example, a phosphate compound represented by the following general formula (2), a condensate thereof, etc. can be cited, but it is not limited thereto. [Chemical formula 2] [Where R 11 , R 12 , R 13 , and R 14

[0047] each independently represents a monovalent group selected from the group consisting of a hydrogen atom, a halogen atom, an alkyl group (preferably having 1 to 12 carbon atoms, more preferably 1 to 6, and further preferably 1 to 3), a cycloalkyl group (preferably having 3 to 24 carbon atoms, more preferably 3 to 12, and further preferably 3 to 6), an aryl-substituted alkyl group (preferably having 7 to 22 carbon atoms, more preferably 7 to 18, and further preferably 7 to 10), an aryl group (preferably having 6 to 22 carbon atoms, more preferably 6 to 18, and further preferably 6 to 10), a halogen-substituted aryl group (preferably having 6 to 22 carbon atoms, more preferably 6 to 18, and further preferably 6 to 10), and an alkyl-substituted aryl group (preferably having 7 to 22 carbon atoms, more preferably 7 to 18, and further preferably 7 to 10), and may be the same as or different from each other; X represents a group containing an arylene group (preferably having 6 to 22 carbon atoms, more preferably 6 to 18, and further preferably 6 to 10); and m is an integer greater than 0]. Furthermore, when the phosphate ester compound is a mixture of phosphate esters and / or condensates thereof having different m, m represents the average value thereof. When m=0, the compound of general formula (2) represents phosphoric acid or a phosphate ester monomer. The phosphate ester compound may be used alone or in combination of two or more.

[0036] Typical examples of the phosphoric acid ester monomer include triphenyl phosphate, tricresyl phosphate, and tricresyl phosphate, but are not limited thereto.

[0037] The phosphorus-based flame retardant is preferably a condensed phosphate ester compound, and more preferably a condensed phosphate ester compound in which m in formula (2) is 1 or more. The upper limit of m may be appropriately defined, and is, for example, 5 or less.

[0038] The phosphorus-based flame retardant is preferably the R 11 , the R 12 , the R 13 And the R 14 At least one of R is an aryl group, a halogen-substituted aryl group, or an alkyl-substituted aryl group. More preferably, the R 11 , the R 12 , the R 13 And the R 14 All of them are aryl groups, halogen-substituted aryl groups, or alkyl-substituted aryl groups. In addition, from the same viewpoint, preferred aryl groups, halogen-substituted aryl groups, and alkyl-substituted aryl groups are preferably phenyl, xylyl, tolyl, or halogenated derivatives thereof.

[0039] The arylene group-containing group represented by X is preferably a residue obtained by removing two hydroxyl groups from phenylene, resorcinol, hydroquinone, bisphenol A, bisphenol F, bisphenol, or a halogenated derivative thereof.

[0040] Examples of the phosphate ester compound include, but are not limited to, resorcinol-bisphenyl phosphate compounds, bisphenol A-polyphenyl phosphate compounds, and bisphenol A-polycresyl phosphate compounds.

[0041] Examples of the condensed phosphate ester compound include compounds of the following formulae (3-1), (3-2), (4-1), and (4-2). [Chemical formula 3] [Chemical formula 4] [Chemical formula 5] [Chemical formula 6] In formula (3-1), (3-2), (4-1), and formula (4-2), Q 1 , Q 2 , Q 3 and Q 4 are substituents, and each independently represents an alkyl group having 1 to 6 carbon atoms, R 7 and R 8 Each independently represents a hydrogen atom or a methyl group. n1 and n2 each independently represent an integer of 0 to 2, and m1, m2, m3 and m4 each independently represent an integer of 0 to 3. In formulas (3-1) and (4-1), Q does not exist. 1 etc., but it is understood that there are Q 1 The same is true for the following.

[0042] In the condensed phosphate esters represented by formula (3-1), (3-2), (4-1), and formula (4-2), n is an integer of 1 or more, and preferably an integer of 1 to 3.

[0043] Among them, in formula (3-1), (3-2), (4-1), and formula (4-2), R is preferably 7 and R 8 is a condensed phosphate ester of methyl, and Q 1 , Q 2 , Q 3 , Q 4All are methyl groups, n1 and n2 are 0, m1, m2, m3 and m4 are independently condensed phosphates of integers from 0 to 3, and the range of n is 1 to 3. Among them, it is particularly preferred that the component contains 50% by mass or more of a phosphate ester in which n is 1. Such flame retardants can also use commercial products, for example, commercial products manufactured by Daihachi Chemical Co., Ltd. under the trade names of "CR-741", "CR733S", and "PX-200". As phosphate esters, specifically, bisphenol A bis(diphenyl phosphate) and resorcinol dixylyl phosphate are most preferred.

[0044] Regarding the compounds of formula (3-1), (3-2), (4-1), and formula (4-2), reference can be made to those disclosed in Japanese Patent Application Laid-Open No. 2010-123933.

[0045] Specific examples of the phosphorus-based flame retardant include compounds represented by the following formula (5) or (6). [Chemical formula 7]

[0046] Regarding the content of the phosphorus-based flame retardant in the modified polyphenylene ether resin foamed sheet of the present embodiment, from the viewpoint of being able to obtain a resin composition with better foamability, heat resistance and flame retardancy, when the total of the polyphenylene ether resin, the polystyrene resin and the phosphorus-based flame retardant is set to 100 mass%, it is preferably 5 mass% to 20 mass%, and more preferably 7 mass% to 15 mass%.

[0047] (Halogen flame retardant) The modified polyphenylene ether resin foam sheet of the present invention is preferably a resin material containing a specific halogen flame retardant as a constituent. The halogen atom contained in the halogen flame retardant is not particularly limited, but is preferably bromine or chlorine, and more preferably bromine. The halogen flame retardant is preferably a brominated carbonate oligomer or brominated polystyrene. As the halogen-based flame retardant, a compound having a bisphenol skeleton is preferred, and specifically, a compound (brominated carbonate oligomer) having the following structural formula (Formula (7)) is preferred.

[0048] [Chemical formula 8] R 21 and R 22 represents a halogen atom or an alkyl group. The halogen atom is preferably a bromine atom. The alkyl group is preferably an alkyl group having 1 to 12 carbon atoms, more preferably an alkyl group having 1 to 6 carbon atoms, and further preferably an alkyl group having 1 to 3 carbon atoms. 23 and R 24represents a hydrogen atom or an alkyl group having 1 to 3 carbon atoms. z and v represent integers of 0 to 5. O is a natural number arbitrarily determined according to the molecular weight, and is preferably 4 to 15.

[0049] Specific examples of the halogen-based flame retardant include compounds represented by the following formula (7-1) or (7-2). [Chemical formula 9] n is 4 to 15 (molecular weight is about 3,000 to about 10,000). [Chemical formula 10] n is 4 to 15 (molecular weight is about 2,500 to about 9,000).

[0050] As another embodiment different from the above, the halogen flame retardant is preferably brominated polystyrene having a repeating structural unit represented by the following formula (8): wherein x represents a natural number of 500 to 10,000, and y represents a natural number of 1 to 5. [Chemical formula 11]

[0051] From the perspective of maintaining the foamability of the resin, the molecular weight of the halogen flame retardant is important, and it is preferably an oligomer or polymer with a weight average molecular weight of 1,000 to 1,000,000, and preferably an oligomer or polymer with a weight average molecular weight of 5,000 to 800,000 (50,000 in the case of an oligomer). If the molecular weight is less than the lower limit, it is recognized as a foreign matter during foaming and causes gas diffusion, hindering foamability. In addition, if the molecular weight exceeds the upper limit, bubble growth is inhibited and a foam of the desired density cannot be obtained. However, in the case of brominated carbonate oligomers, it is preferably within the range, and on the other hand, in the case of high-polymerization polymers such as brominated polystyrene, the upper limit is higher, preferably less than 1,000,000. Furthermore, in this specification, when "molecular weight" is mentioned, it refers to "weight average molecular weight" unless otherwise specified. The method for determining the weight average molecular weight is as described above.

[0052] The amount of the halogen flame retardant is not particularly limited. When the total amount of the polyphenylene ether resin, the polystyrene resin and the phosphorus flame retardant is set to 100 parts by mass, the halogen flame retardant is preferably 5 parts by mass to 40 parts by mass, more preferably 10 parts by mass to 40 parts by mass, and further preferably 20 parts by mass to 40 parts by mass.

[0053] <Resin density and expansion ratio> The density of the resin constituting the modified polyphenylene ether resin foamed sheet of the present invention is preferably 0.60 g / cm3 ~0.10g / cm 3 , more preferably 0.50 g / cm 3 ~0.15g / cm 3 , further preferably 0.30 g / cm 3 ~0.15g / cm 3 . The density of the resin is an indicator that can be used to understand the degree of foaming, and in this respect it is a variable similar to the foaming ratio. In the resin of the present invention, the foaming ratio is preferably 2 to 12 times, more preferably 2 to 10 times, 2 to 7 times. The density (foaming ratio) of the resin being in the above range means that there are more bubbles in the foamed sheet, which is close to the dielectric constant of air, and a low dielectric constant of the relative dielectric constant can be achieved.

[0054] <Average bubble diameter> In the modified polyphenylene ether resin foam sheet of the present invention, the average bubble diameter of the bubbles present in the resin constituting it needs to meet 1 to 30 μm. Here, the lower limit of the average bubble diameter is more than 1.0 μm, and more preferably more than 1.5 μm. The upper limit is less than 30 μm, preferably less than 28 μm, more preferably less than 26 μm, further preferably less than 22 μm, and further preferably less than 18 μm. In addition, the average bubble diameter is further preferably less than 12 μm, more preferably less than 10 μm, and most preferably less than 8 μm. In the foam sheet of the present invention, there is the following advantage, that is, the smaller the average diameter of the bubbles as described, the better the forming processability, the better the realization of low relative dielectric constant and low dielectric loss factor, and the surface characteristics with smaller surface roughness can be achieved.

[0055] <Bubble number density> Here, the smaller the average bubble diameter of the foamed sheet is, the better the relative dielectric constant as a dielectric property is. However, if the foaming ratio is low, the bubble density in the cross section of the sheet occupied by the resin foamed sheet is low. As a result, the ratio of the resin component becomes larger, so the probability of the existence of the part without bubbles around the bubbles becomes higher, and at the same time, the thickness of the pore wall of the bubble becomes thicker. Therefore, in order to reduce the relative dielectric constant, it is not enough to simply reduce the bubble diameter. The loss generated by the part without bubbles or the bubble wall will increase. Therefore, it is preferred to reduce the bubble diameter of the foamed sheet and at the same time make the bubble number density of the cross section of the foamed sheet a certain degree of high value. That is, in order to improve the dielectric properties (relative dielectric constant and tanδ) of the foamed sheet of the present invention, not only is the average bubble diameter of the foamed body set to a specified range of 1 to 30 μm, ideally 1 to 22 μm, but the bubble number density needs to be set higher. Based on this viewpoint, the bubble number density of the foamed sheet of the present invention is 1.8×10 4 ~9.0×10 8 Pieces / mm3 , or 2.0×10 4 ~9.0×10 8 Pieces / mm 3 , preferably 1.0×10 5 ~9.0×10 8 Pieces / mm 3 , more preferably 1.0×10 6 ~9.0×10 8 Pieces / mm 3 , and further preferably 3.0×10 6 ~7.5×10 8 Pieces / mm 3 .

[0056] <Manufacturing method of foamed sheet (micro-foaming process)> The fine foaming method is a batch method, and the steps are as follows: first, in a high-pressure container, a high-pressure inert gas (for example, nitrogen or carbon dioxide) is fully dissolved as a foaming agent in a solid resin sheet at room temperature until the saturated solubility of the gas is reached, and then the gas in the high-pressure container is depressurized or heated, thereby utilizing the thermodynamic instability of the gas contained in the resin to cause phase separation, thereby foaming the resin. As a specific step example, for example, a method that goes through the following three steps. First, in the method for manufacturing a polyphenylene ether resin foam sheet of the present embodiment, a step of making the resin contain a non-reactive gas under pressure is adopted (hereinafter referred to as "the first step"). Subsequently, the step of heating the obtained thermoplastic resin in a temperature range above the crystallization peak temperature of the resin measured by a differential scanning calorimeter and below the melting point peak temperature to foam the resin (hereinafter referred to as "the second step"). Finally, a step of cooling the obtained thermoplastic resin is adopted (hereinafter referred to as "the third step"). The average cell diameter of the foamed sheet can be adjusted by the holding time and the holding temperature in the second step.

[0057] <Surface roughness> When an alternating current flows through a conductor, there is a skin effect, that is, the higher the frequency of the current, the less likely it is to flow to the center of the conductor, and only to flow to the surface. In addition, the relationship between the surface roughness and transmission loss of a high-frequency copper circuit is that if the surface roughness is greater than the epidermis depth, the signal transmission path becomes longer and the signal loss becomes more. On the contrary, if the roughness is less than the epidermis depth, the transmission is smaller, the transmission path becomes shorter, and the signal loss becomes less. Therefore, the lower the surface roughness of the foam sheet, the better. In particular, in high-frequency bands such as GHz bands or THz bands, the surface properties of the foam sheet will affect the surface properties of the circuit material and there is a possibility of affecting the loss. In addition, in resin foam sheets that are expected to be used in circuit substrate materials, etc., considering the further high-precision of the circuit in the future, and considering the influence of the roughness of the substrate surface on the surface properties of the stacked circuit, it is necessary to reduce the surface roughness of the foam sheet. Here, as the surface roughness, since the uniform roughness of the sheet surface is important, the surface roughness in the present invention uses the arithmetic average surface roughness Ra. Based on this viewpoint, the surface roughness Ra of the polyphenylene ether resin foam sheet is 0.10 to 0.50 μm, preferably 0.10 to 0.35 μm, more preferably 0.10 to 0.30 μm, and further preferably 0.10 to 0.25 μm. In this way, the reason why the surface roughness of the resin foam sheet of the present invention as a surface quality is excellent is that in the fine foaming method, since the gas permeation step and the foaming step in this foaming method are separated, the bubble diameter can be made smaller and the bubble diameter distribution can be made more stable. Therefore, the surface properties are easily stabilized, and by combining the roller processing as described above, the arithmetic mean surface roughness Ra, which is an indicator of surface roughness, can be suppressed to a lower level.

[0058] <Relative dielectric constant, dielectric loss factor> Since the foam sheet has a low relative dielectric constant and a low dielectric loss factor, it can exert suitable performance when used for housings for electrical parts, housings for electronic parts, electrical insulating materials, sealing materials, protective materials, high-frequency substrates, or substrates for electromagnetic wave control components. Based on this viewpoint, the relative dielectric constant of the foam sheet is preferably 1.10 to 2.00, more preferably 1.10 to 1.60, further preferably 1.10 to 1.50, and most preferably 1.10 to 1.35. The dielectric loss factor (tan δ) is preferably 0.5×10 -3 ~2.5×10 -3 , more preferably 0.7×10 -3 ~2.2×10 -3 , and the most preferred value is 1.0×10 -3 ~2.0×10 -3 , and further ideally 1.0×10 -3 ~1.8×10-3 , or 1.0×10 -3 ~1.5×10 -3 . In addition, the relative dielectric constant is a value measured by the method described in the examples. [Example]

[0059] (Measurement method) The expansion ratio and the foam density were measured as follows. <Measurement method of foaming ratio> The expansion ratio is the apparent ratio commonly used in resin foams. A 10 cm × 10 cm test piece is cut from the foamed resin sheet and weighed (W1 [g]). Subsequently, the thickness of the four corners and the center of the test piece is measured (the measuring machine is based on JIS K6767 method). The average value (T [cm]) of the five points is used to calculate the apparent ratio according to the following formula (1). Apparent ratio (foaming ratio) = 10 × 10 × T / W1 (1)

[0060] <Measurement method of foam density> The density of the resin foam sheet is measured in accordance with JIS K7222-1999 and "Foamed plastics and rubbers - Determination of apparent density". A 10 cm x 10 cm specimen is cut out from the resin foam sheet that has been conditioned at 23°C ± 2°C for 72 hours or more after molding. Specifically, the foam density is calculated according to the following formula (2). The unit is g / cm 3 . [Mathematical formula 1] ρ a ={(m+ma)} / V (2) m is the mass of the specimen (g), V is the volume of the specimen (cm 3 ), ma is the mass of the displaced air (g). Since the expansion ratio was low, ma (mass of replaced air) was negligible, so ma was ignored for calculation. Five measurements were performed, and the average value was calculated from the measurement results of all the test pieces and used as the density.

[0061] <Measurement method of bubble diameter> The bubble diameter is calculated according to ASTM D3576-77. Take a SEM (Scanning Electron Microscope) photograph of the longitudinal section of the sheet, draw straight lines in the horizontal and vertical directions on the SEM photograph, and average the bubble chord lengths t that are crossed by the straight lines. The magnification of the photograph is taken as M, and introduced into the following formula to calculate the average bubble diameter d (d = t / (0.616 × M)). Regarding the average bubble diameter, SEM photographs are measured in three different fields of view, and the average value is taken as the average bubble diameter.

[0062] <Measurement method of bubble number density> A SEM photograph of the longitudinal section of the polyphenylene ether resin foam sheet was taken. Five 100 μm×100 μm areas were randomly selected on the SEM photograph, and the number of bubbles in each area was counted. From each count value, the number of bubbles per 1 mm in each area was calculated. 2 The number of bubbles is calculated based on the area per 1 mm 3 Calculate the number of bubbles per 1mm in each of the five areas. 2 The average value of the number of bubbles is taken as the bubble density (cells / mm 2 ). By dividing the obtained 2 The number of bubbles is multiplied by (3 / 2) and used as the value per 1mm in each area. 3 Calculate the number of bubbles per 1mm in each of the five areas. 3 The average value of the number of bubbles is taken as the bubble density (cells / mm 3 ). When measuring the cell diameter or the cell number density, it is ideal to prepare a plurality of (preferably 3 or more) SEM photographs and average the values ​​calculated in the respective SEM photographs.

[0063] <Measurement of relative dielectric constant and dielectric loss factor> The relative dielectric constant and dielectric loss factor were measured using the cavity perturbation method with the measurement frequency set to 2 GHz. r The dielectric loss factor tanδ and the multiple dielectric constants of the polyphenylene ether resin foam sheet in the plane direction can be measured by the resonant cavity method. In the present invention, the relative dielectric constant is measured by the resonant cavity method at a resonant frequency of 2 GHz using a sample of 78 mm in length × 2.4 mm in width × 1 mm in thickness. As the device used for measurement at this time, for example, the resonant cavity can use CP461 manufactured by Kanto Electronics Application Development Co., Ltd., and the network analyzer can use E8361A manufactured by Agilent Technologies.

[0064] <Measurement of surface roughness> Regarding the evaluation of the surface properties, in order to evaluate the overall surface properties of the modified polyphenylene ether foamed sheet, the surface properties of the foamed sheet of the present invention were evaluated by measuring Ra instead of Rz which is greatly affected by the maximum roughness and the like. According to JIS B0601: 2013, the arithmetic mean roughness of Ra is determined. HANDYSURF E-30A (manufactured by Tokyo Seimitsu Co., Ltd.) was used in the measurement. In each measurement, the standard length was set to 2.5 mm. In the present invention, when the surface roughness Ra is, for example, less than 1.0 μm, it means that on the surface of the modified PPE foam sheet, 5 measurement lines are randomly determined in the MD direction, and the arithmetic mean roughness of the measurement values ​​in each measurement line is measured to obtain the average roughness of the 5 measurement values, and 5 measurement lines are randomly determined in the TD direction. The average value of the average roughness in the two directions is less than 1.0 μm. That is, the surface roughness in the present invention is evaluated by the average value of the two directions of the MD direction and the TD direction. Here, since the surface roughness is affected not only in the MD direction but also in the TD direction as a surface characteristic, the reason for taking the average value of the two directions is that when the sheet is manufactured, it is sometimes passed through rollers. At this time, in addition to the surface pressing effect generated by the rollers in the MD direction of the sheet, tension is also applied to it and it is stretched. Therefore, in many cases, the surface properties in the MD direction are better than those in the TD direction.

[0065] <Flame retardancy test> As a flame retardancy test, as a flame retardancy grade, as an evaluation of whether the flame retardancy can be improved even slightly by a flame retardant, the following two layers are set: an evaluation of the oxygen index based on the plastic combustibility test based on JIS K 7201-2:2021 as an evaluation of flammability, self-extinguishing property with flammability, flame retardancy, etc.; and in the flame retardancy test of the UL94 standard, satisfying V-0 and V-1 in the vertical flame retardancy test.

[0066] [Plastic flammability test based on JIS K 7201-2] Under the specified test conditions, at a temperature of 23℃±2℃ at which the material can sustain flaming combustion, the minimum oxygen volume fraction in the mixture of oxygen and nitrogen is expressed as a percentage (%). The test is carried out in a transparent cylinder where a mixture of oxygen and nitrogen flows upward in a laminar flow using a test piece mounted on a specified test piece support tool. The test is carried out at room temperature after the adjustment state. In the procedure of upper end ignition, the flame is kept in contact with the upper end of the test piece for 30 seconds, and the flame is removed every 5 seconds to confirm whether the test piece is burning. This method is to avoid a continuous increase in the temperature of the test piece, because a temperature increase usually reduces the oxygen index. In addition, the test is carried out in accordance with the JIS standard, but some records are omitted.

[0067] [UL94 flame retardancy test: vertical flame retardancy test] According to UL94 (standard specified by Under Writers Laboratories Inc., USA), the obtained sheet was used to make 5 test pieces with a length of 125 mm and a width of 13.0 mm, and a vertical flame retardancy test was performed. In the test, each test piece was vertically mounted on a fixture and subjected to flame contact with a 20 mm flame for 10 seconds twice. According to its burning behavior, it was judged as V-0, V-1, and V-2. Here, the flame retardancy standards of V-0, V-1, and V-2 are as follows.

[0068] [Evaluation standard of oxygen index in plastic flammability test based on JIS K 7201-2] In general, the oxygen index is understood as follows. 22 or less: flammable and burning 23-27: Burns but self-extinguishes 27 or above: Flame retardant

[0069] [Flame retardant standards of V-0, V-1, and V-2] V-0: The duration of the first and second flaming combustions was both within 10 seconds. Furthermore, the total duration of the second flaming combustion and the flameless combustion time was within 30 seconds. Furthermore, the total flaming combustion time of the five test pieces was within 50 seconds. No sample burned to the position of the fixing fixture, and the cotton was not ignited by the burning drops. V-1: The duration of the first and second flaming combustions was both within 30 seconds. Furthermore, the total duration of the second flaming combustion and the flameless combustion time was within 60 seconds. Furthermore, the total flaming combustion time of the five test pieces was within 250 seconds. No sample burned to the position of the fixing fixture, and the cotton was not ignited by the burning drops. V-2: The duration of the first and second flaming combustions was both within 30 seconds. Furthermore, the total duration of the second flaming combustion and the flameless combustion time was within 60 seconds. Furthermore, the total flaming combustion time of the five test pieces was within 250 seconds. No sample burned to the position of the fixing fixture, and the burning debris ignited the cotton. Furthermore, in the vertical flame retardancy test, samples that did not meet any of the standards of V-0, V-1, and V-2 were marked as unqualified (×).

[0070] Modified polyphenylene ether resin used Modified polyphenylene ether (hereinafter referred to as m-PPE): Zylon 340Z manufactured by Asahi Kasei Co., Ltd. A composition comprising polyphenylene ether containing poly-2,6-dimethyl-1,4-phenyl oxide, polystyrene and a phosphorus-based flame retardant (a phosphate-based compound of the formula (5) or (6)). Here, the polystyrene is high-impact polystyrene. Modified polyphenylene ether (hereinafter referred to as m-PPE): Zylon 540Z manufactured by Asahi Kasei Co., Ltd. A composition comprising polyphenylene ether containing poly-2,6-dimethyl-1,4-phenyl oxide, polystyrene and a phosphorus-based flame retardant (a phosphate-based compound of the formula (5) or (6)). Here, the polystyrene is an impact-resistant polystyrene.

[0071] Flame retardant (1): Fire Guard FG-8500 manufactured by Teijin Co., Ltd. (compound of the above formula (7-1))

[0072] Flame retardant (2): Fire Guard FG-7500 manufactured by Teijin Co., Ltd. (compound of the formula (7-2))

[0073] Flame retardant (3): SAYTEX HP7010G manufactured by Albemarle Japan (The compound represented by the chemical formula (8), x and y are about 2000 and 2.7 respectively, and the molecular weight is about 700,000)

[0074] Flame retardant (4): FR-1410 manufactured by ICL Japan (the following formula (a)) [Chemical formula 12] Molecular weight: 971.2

[0075] Flame retardant (5): SAYTEX 8010 manufactured by Albemarle Japan The same compound as the chemical formula (a) (different manufacturers).

[0076] First, the following 12 test materials were used in the experiment. <Test materials used for testing> Test materials 1 to 8 were prepared by using modified polyphenylene ether (hereinafter referred to as m-PPE): Zylon 540Z manufactured by Asahi Kasei Co., Ltd. as a base and mixing a predetermined amount of flame retardant therein. Here, in test materials 1 to 3, 20 parts, 30 parts, and 35 parts of Fire Guard FG-8500 manufactured by Teijin Co., Ltd. as a flame retardant were mixed with Zylon 540Z as a modified PPE, respectively. In addition, in test materials 4 and 5, 20 parts and 30 parts of Fire Guard FG-7500 manufactured by Teijin Co., Ltd. as a flame retardant were mixed with Zylon 540Z as a modified PPE, respectively. Furthermore, in test materials 6, 7, and 8, 20 parts, 30 parts, and 40 parts of SAYTEX HP7010G manufactured by Albemarle Japan Co., Ltd. as a flame retardant were mixed with Zylon 540Z as a modified PPE, respectively. Here, test materials 1 to 8 are prepared by using Zylon 540Z, a modified PPE, as a base material and further adding predetermined amounts of three different flame retardants having specific molecular weights thereto. Test materials 9 and 10 are foam sheets made of modified polyphenylene ether (modified PPE): Zylon 340Z manufactured by Asahi Kasei Co., Ltd. and foam sheets made of modified polyphenylene ether (hereinafter referred to as modified PPE): Zylon 540Z manufactured by Asahi Kasei Co., Ltd. respectively, but with different product numbers. In test materials 9 and 10, no flame retardant other than the phosphorus-based flame retardant originally contained in Zylon 340Z and Zylon 540Z was added. Test materials 11 and 12 are respectively a foam sheet of a material used in a modified polyphenylene ether (modified PPE): Zylon 340Z manufactured by Asahi Kasei Co., Ltd., to which 20 parts of FR-1410 manufactured by ICL Japan are added as a flame retardant (4), and a foam sheet of a material used in a modified polyphenylene ether (hereinafter referred to as modified PPE): Zylon 540Z manufactured by Asahi Kasei Co., Ltd., to which 20 parts of SAYTEX 8010 manufactured by Albemarle Japan Co., Ltd. are added as a flame retardant (5). Test materials 9 and 11 are both made of Zylon 340Z manufactured by Asahi Kasei Co., Ltd., and test materials 10 and 12 are made of Zylon 540Z manufactured by Asahi Kasei Co., Ltd. Since Zylon 540Z and Zylon 340Z are both PPEs in which PS is blended, considering the difference in glass transition temperatures Tg between PPE and PS, it is believed that the more PS blended in PPE, the lower Tg, and therefore it is believed that the PS content of Zylon 340Z is greater than that of Zylon 540Z.

[0077] <Manufacturing of test material foam sheet> A rolled body of a foamed sheet containing the test material shown in Table 1 was obtained, and the rolled body was placed in a pressure vessel, and the pressure vessel was pressurized to 5.2 MPa with carbon dioxide, and carbon dioxide was allowed to permeate the resin film for 24 hours. Subsequently, the rolled body was taken out of the pressure vessel, and was continuously supplied to a hot air circulation foaming furnace set at 160° C. and kept for a predetermined time to foam it, thereby obtaining each PPE foamed sheet shown in Table 1. At this time, foaming was inhibited in test materials 11 and 12, and almost no foaming occurred, and the target foam could not be obtained. In addition, in test materials 7 and 8, the foaming temperature was set to 170°C. In test materials 9 and 10, the foaming temperature was set to 180°C.

[0078] <Test material foam sheet property evaluation test results> Table 1 shows the results of property tests using test materials 1 to 12 as test materials.

[0079] <Foaming properties of modified PPE foam sheets and properties related to cell structure> The foamability of the test materials was evaluated based on the expansion ratio and density. Since the test materials 1 to 8 and the test materials 9 and 10 except the test materials 11 and 12 could be properly foamed, the expansion ratio was in the range of 2 to 10 times, specifically in the range of 2.8 to 6.8 times, and the foam density was in the range of 0.10 to 0.50, specifically in the range of 0.17 to 0.41. In contrast, the test materials 11 and 12 had an expansion ratio of only 1.1 due to the foaming hindrance caused by the addition of the flame retardant, and there was almost no density change caused by foaming, which was only 1.07 to 1.08, and the target foamed sheet was not obtained. As evaluation parameters for evaluating the cell structure of the foam, the cell diameter (average cell diameter) and the cell number density are used. The test results show that the average cell diameter is within the range of 1 to 22 μm, specifically, within the range of 1.7 to 21.2 μm, and the cell number density is 10 4 The above is the goal, and the actual satisfaction is 2.0×10 4 ~7.2×10 8 Pieces / cm 3 The modified resin foamed sheet of the present invention has a predetermined average cell diameter and cell number density.

[0080] <Dielectric properties of modified PPE foam sheets> The relative dielectric constant and dielectric loss factor (tanδ) of the dielectric properties of test materials 1 to 8 were tested using the resonant cavity perturbation method and a network analyzer. The results showed that the average bubble diameter was 1 to 22 μm and the bubble number density was 10 4 The relative dielectric constant of test materials 1 to 8 is 1.20 to 1.57, and the dielectric loss factor tanδ is 1.0×10 -3 ~1.5×10 -3 The relative dielectric constant of test material 8 and test material 9 is 1.20, and the dielectric loss factor tanδ is 1.0×10 -3 ~2.1×10 -3 Regardless of whether polymer flame retardants are added, the relative dielectric constant and dielectric loss factor are excellent. In addition, since the average bubble diameter of test materials 1 to 10 is within the range of 1.7 to 21.2 μm, which is less than 22 μm, it is expected that not only the dielectric properties in the gigahertz band will be good, but also the diffuse reflection loss will be small when passing through the foamed sheet in terms of the comparison between the wavelength and the average bubble diameter. Here, for test materials 11 and 12, since foaming was not obtained due to the occurrence of foaming hindrance, the dielectric properties were not evaluated.

[0081] <Surface properties of modified PPE foam sheets> For test materials 1 to 8 and test materials 9 and 10, except for test materials 11 and 12, which are foam sheets that did not obtain normal foaming, the average value of the results of Ra measurements performed 5 times in the MD direction and TD direction of the foam surface is shown as the surface characteristics of the modified PPE sheet. The result of measuring the arithmetic average surface roughness Ra is shown as the surface roughness. Although the surface roughness of test materials 3 and 8 is relatively large, even when test materials 3 and 8 are included, the arithmetic average surface roughness Ra is still in the range of 0.10 to 0.30 μm below 0.5 μm. Except for test materials 3 and 8, the difference in arithmetic average roughness Ra between materials is small, and Ra is in the range of 0.10 to 0.14 μm, which satisfies 0.20 μm or less. Furthermore, regarding the arithmetic average surface roughness Ra of the present invention, even if the upper limit of the arithmetic average surface roughness Ra is considered to be 0.5 μm or less, it is considered that its surface characteristics are better than the surface roughness obtained by bead foaming, etc. Here, regarding Test Materials 11 and 12, since foaming inhibition occurred and a foamed sheet could not be obtained, the surface properties were not evaluated.

[0082] <Flame retardancy of modified PPE foam sheets> The evaluation results of the flame retardancy test of each test material in Table 1 are shown. In the table, the oxygen index is recorded as the OI value. According to the results of the vertical flame retardancy test of UL94, the oxygen index of the modified PPE foam sheets of test materials 1 to 8 in which a specified amount of phosphorus-based flame retardant and polymer-based flame retardant were added to the modified PPE foam sheet was in the range of 27.4 to 32.5, exceeding 27 as the oxygen index flame retardancy standard, and clearly meeting the V-0 and V-1 standards of UL94. In contrast, in the test material 9 made of Zylon 340Z foamed sheet to which only phosphorus flame retardant is added to the modified PPE foamed sheet, and the test material 10 made of Zylon 540Z foamed sheet to which only phosphorus flame retardant is added, the addition of flame retardant does not cause foaming hindrance. Although the effect of improving the oxygen index can be confirmed, the oxygen index is 24.8 and 25.4. Compared with the test materials 1 to 8, although it has self-extinguishing properties, it lacks flame retardancy and fails to meet V-0 to V-1 of the UL94 standard. In addition, since the oxygen index of test materials 1 to 8 exceeds 27, it is considered to have flame retardancy. Here, when only phosphorus flame retardant is added, since the content of flame retardant is small and polymer flame retardant is not contained, compared with the non-flame retardant grade modified PPE without flame retardant, the flame retardancy is improved due to the addition of flame retardant, but V-0 to V-1 of UL-94 is not satisfied. Here, although not necessarily described in the examples, when described only as a reference, when the test materials 8 and 9 were not foamed but subjected to a flame retardancy test according to the UL standard in an unfoamed state, it was confirmed that the V-0 standard was satisfied.

[0083] In contrast, in the test materials 11 and 12 to which a halogen flame retardant having a molecular weight of less than 1,000 was added, since the amount of the flame retardant was increased by adding a halogen flame retardant in addition to the phosphorus flame retardant, the oxygen index was higher than that of the case where only the phosphorus flame retardant was added, which was 29.3 and 29.5, and the flame retardancy was improved. Although the flame retardancy met the V-0 standard of UL94, the addition of such flame retardant caused the foaming of the modified PPE to be hindered, and the modified PPE foamed sheet could not be obtained due to the foaming hindrance. In the present invention, the reason why a polymer flame retardant higher than a oligomer is used as a halogen flame retardant is that low molecular flame retardants or metal hydroxide flame retardants, which are usually used as flame retardants, do not cause the expansion of the flame retardant at high temperatures due to the foaming gas, the foaming gas does not penetrate into the flame retardant, and thus, this phenomenon becomes a cause of foaming hindrance. However, in the case of a polymer flame retardant, carbon dioxide can penetrate into the flame retardant and further has suitable viscoelasticity at high temperatures near the foaming temperature. Therefore, it is believed that no foaming hindrance will be caused and a foamed body with fine bubbles can be formed.

[0084] <Summary of test results> In summary, in order to obtain the modified PPE foam sheet of the present invention, as shown in test materials 9 and 10, in the case of adding a specified amount of phosphorus-based flame retardant to a modified PS resin in which a specified range of PS is added to PPE, a foam sheet having a suitable bubble structure or dielectric properties and excellent surface properties is obtained, but since the amount of flame retardant added is small, although the flame retardancy is improved, even if it is flammable, it is successfully given self-extinguishing properties, but a foam sheet that meets the UL standard for flame retardancy cannot be obtained. In addition, in order to ensure flame retardancy, as shown in test materials 11 and 12, a low molecular weight halogen-based flame retardant is added, and although the flame retardancy meets the UL standard, it causes foaming hindrance and fails to obtain the specified foam sheet. In contrast, in the case of the foamed sheets of test materials 1 to 8, in addition to the phosphorus-based flame retardant, a high-molecular flame retardant having a weight average molecular weight of 1,000 to 1,000,000 higher than the oligomer is added as a flame retardant, and a foamed sheet having excellent bubble structure, dielectric properties, and surface properties and excellent flame retardancy without causing foaming hindrance can be obtained. Furthermore, since the modified PPE foamed sheet of the present invention has excellent dielectric properties and a small average bubble diameter, when it is used for a circuit substrate in the gigahertz band, not only can the transmission loss be suppressed to a low level, but also the diffuse reflection loss can be suppressed to a low level. At the same time, when a conductor such as copper foil forming a circuit is loaded on the present foamed sheet, since the surface properties of the foamed sheet are excellent, the influence of the skin effect of the base foamed sheet on the circuit or conductor can be reduced. The above requirements of cell structure, cell density, surface characteristics and flame retardancy can be preliminarily achieved by combining the foaming step with the batch-type modified PPE resin micro-foaming step and by combining the phosphorus flame retardant with the halogen-based polymer flame retardant having a specified molecular weight higher than the oligomer in the flame retardant. Furthermore, according to the present invention, a thin-walled modified PPE foam sheet with a thickness as low as 50 μm can be obtained.

[0085] <Research> As shown in Table 1, the modified polyphenylene ether foamed sheets of test materials 1 to 8 are mixed with halogen flame retardants (1) to (3) and exhibit excellent flame retardancy (UL94V-0). On the other hand, despite the presence of the halogen flame retardant, the electrical properties (relative dielectric constant, dielectric loss factor) are not significantly affected, and the electrical properties are comparable to those of the modified polyphenylene ether foamed sheets of test materials 9 and 10 that do not contain the halogen flame retardant but only contain a specified amount of phosphorus flame retardant. That is, in the present invention, when using fine foaming method to make modified polyphenylene ether foam, even if only adding a prescribed amount of phosphorus flame retardant also improves flame retardancy, but the foam that meets UL94 standard cannot be obtained, by combining phosphorus flame retardant with halogen flame retardant with prescribed molecular weight, it is possible to obtain the foam that maintains the surface quality of foam sheet, the relative dielectric constant and dielectric loss factor under high frequency are very low, and flame retardancy is higher, and the foam sheet that meets V-0 and V-1 performance of UL94 standard is satisfied. At this time, the advantage is also that, although crosslinking agent or bubble nucleating agent can also be used, the modified polyphenylene ether foam sheet can also be obtained when crosslinking agent or bubble nucleating agent is not used. Due to the clear phosphorus flame retardant that only a prescribed amount is added, there is the effect of improving flame retardancy, and if judged according to the oxygen index grade, it is believed that although it has combustibility, it has self-extinguishing property, and the bubble structure, dielectric properties, and surface properties of the foam are excellent, so it can be fully used according to use purpose or use form.

Claims

1. A modified polyphenylene ether resin foam sheet, characterized in that: The modified polyphenylene ether resin foam sheet is obtained by foaming a modified polyphenylene ether resin containing a flame retardant, and has a relative dielectric constant of 1.10 to 2.00 and a dielectric loss factor (tan δ) of 0.5×10 -3 ~2.5×10 -3 range.

2. The modified polyphenylene ether resin foamed sheet according to claim 1, wherein The surface of the modified polyphenylene ether resin foamed sheet has an arithmetic mean surface roughness Ra of 0.50 μm or less.

3. The modified polyphenylene ether resin foamed sheet according to claim 1, wherein The modified polyphenylene ether resin foamed sheet contains only a phosphorus-based flame retardant as the flame retardant.

4. The modified polyphenylene resin foam sheet according to claim 1, wherein The modified polyphenylene ether resin foam sheet contains, as the flame retardant, both a halogen-based flame retardant and a phosphorus-based flame retardant having a weight average molecular weight of 1,000 to 1,000,000.

5. The modified polyphenylene ether resin foamed sheet according to claim 3 or 4, wherein The modified polyphenylene ether resin foamed sheet has a relative dielectric constant of 1.20 to 1.57 and a dielectric loss factor (tan δ) of 1.0×10 -3 ~2.1×10 -3 range.

6. A modified polyphenylene ether resin foam sheet, wherein: The modified polyphenylene ether resin foam sheet is a modified polyphenylene ether resin foamed sheet obtained by foaming a modified polyphenylene ether resin containing both a halogen flame retardant and a phosphorus flame retardant having a weight average molecular weight of 1,000 to 1,000,000 as flame retardants, wherein the average bubble diameter of the bubbles in the modified polyphenylene ether resin foam sheet is 1 to 30 μm, and the bubble number density is 1.8×10 4 ~9×10 8 Pieces / mm 3 .

7. The modified polyphenylene ether resin foamed sheet according to claim 6, wherein In the modified polyphenylene ether resin foamed sheet, the average bubble diameter of the bubbles in the modified polyphenylene ether resin foamed sheet is 1 to 22 μm, and the bubble number density is 2.0×10 4 ~8×10 8 Pieces / mm 3 .

8. The modified polyphenylene ether resin foamed sheet according to claim 1 or 6, wherein The modified polyphenylene ether resin foamed sheet has an average thickness of 0.05 mm to 2.0 mm.

9. The modified polyphenylene ether resin foamed sheet according to claim 4 or 6, wherein The modified polyphenylene ether resin foam sheet was tested according to the UL-94 vertical method (20 mm vertical burning test) of the US UL standard and the flame retardancy was evaluated. The test result satisfied the V-0 or V-1 standard.

10. The modified polyphenylene ether resin foamed sheet according to claim 1 or 6, wherein The modified polyphenylene ether resin foam sheet is used for housings for electric parts, housings for electronic parts, electric insulating materials, sealing materials, protective materials, high-frequency substrates, or substrates for electromagnetic wave control components.

11. A housing for electric parts, a housing for electronic parts, an electric insulating material, a sealing material, a protective material, a high-frequency substrate, or a substrate for an electromagnetic wave control member, which is obtained by using the modified polyphenylene ether resin foam sheet according to claim 1 or 6.

Citation Information

Patent Citations

  • Threshing device using compressed air

    JP1981042521A

  • Side heating type crucible

    JP1983009895A

  • Connecting rod

    JP1986006420A

  • Foamed body for substrate

    JP2008303247A

  • Connection structure for photovoltaic power generation module

    JP2010123933A

Cited By

  • High-precision polyphenyl ether foaming material and preparation method thereof

    CN121930536A